Pengaruh Kecerdasan Spiritual dan Karakter Integritas terhadap Perilaku Kejujuran Akademik Mahasiswa Magister Pendidikan Agama Islam di Universitas Islam Negeri Sultan Syarif Kasim Riau - Witari Triarni Panggabean; Amril M; Muslim Afandi (LPPM Institut Pendidikan Nusantara Global, 2026)
This study aims to determine the influence of spiritual intelligence and integrity character on the academic honesty behavior of Postgraduate Islamic Religious Education Study Program Students at Sultan Syarif Kasim State Islamic University, Riau. This research is a field research with a quantitative approach. The population in this study were 90 Postgraduate Islamic Religious Education Students, while the sampling technique used was stratified random sampling of 73 Students. Data collection techniques used observation, questionnaires and documentation. Data analysis techniques used linear and multiple regression. The results of this study indicate that; 1) There is an influence of Spiritual Intelligence that has a significant influence on the Academic Honesty Behavior of Postgraduate Islamic Religious Education Study Program Students at Sultan Syarif Kasim State Islamic University, Riau. This is indicated by the calculated t result being greater than the t table (5.165> 1.99) with a sig. value of 0.000 <0.005. It can also be seen from the results of R2 = 0.273 meaning 27.3%. 2) There is an influence of Integrity Character that has a significant influence on the Academic Honesty Behavior of Postgraduate Islamic Religious Education Study Program Students at Sultan Syarif Kasim State Islamic University, Riau. This is indicated by the calculated t result which is greater than the t table (3.067 > 1.99) with a sig. value of 0.003 < 0.005. It can also be seen from the results of R2 = 0.117 meaning 11.7%. 3) There is a significant influence between Spiritual Intelligence and Integrity Character simultaneously on the Academic Honesty Behavior of Postgraduate Islamic Religious Education Study Program Students at Sultan Syarif Kasim State Islamic University, Riau. This is indicated by the calculated F value > F table (16.442 > 3.12). In addition, the results of the determination analysis that looks for the percentage contribution of the influence of independent variables simultaneously on the dependent variable is 32.0%. While the remaining 68% is contributed by other variables not discussed in this study.